2015
DOI: 10.1089/ten.tea.2013.0719
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Encapsulated Nucleus Pulposus and Bone Marrow Stem Cells in Isolation and Coculture in Alginate and Chitosan Hydrogels

Abstract: Cell-based therapies may hold significant promise for the treatment of early stage degeneration of the intervertebral disc (IVD). Given their propensity to proliferate and ability to form multiple tissue types, mesenchymal stem cells (MSCs) have been proposed as a potential cell source to promote repair of the nucleus pulposus (NP). However, for any successful cell-based therapy a carrier biomaterial may be essential for targeted delivery providing key biophysical and biochemical cues to facilitate differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 59 publications
3
56
0
Order By: Relevance
“…An optimization of the cell ratio between chondrocytes and stem cells is however needed for the optimal outcomes of this coculture system. Seeding 2 and 4 times more BMSCs than chondrocytes was more effective than equal quantities in polymer gels . Similarly, a primary human chondrocytes:BMSC ratio of 1:3 leads to the highest chondro‐induction on collagen mesh in vitro .…”
Section: Tissue‐specific Coculture Processesmentioning
confidence: 87%
“…An optimization of the cell ratio between chondrocytes and stem cells is however needed for the optimal outcomes of this coculture system. Seeding 2 and 4 times more BMSCs than chondrocytes was more effective than equal quantities in polymer gels . Similarly, a primary human chondrocytes:BMSC ratio of 1:3 leads to the highest chondro‐induction on collagen mesh in vitro .…”
Section: Tissue‐specific Coculture Processesmentioning
confidence: 87%
“…There have also been reports of increases in chondrogenic markers through soluble paracrine signalling (Ahmed, Dreier, Göpferich, Grifka, & Grässel, ; Aung, Gupta, Majid, & Varghese, ). One study that investigated the co‐culture of nucleus pulpous (NP) cells and BMSC showed a large increase in the DNA of NP cells while the “supporting” BMSC population decreased in number (Naqvi & Buckley, ). Other studies have observed a similar phenomenon of “chondro‐induction” mediated by two concomitant effects: MSC‐induced chondrocyte proliferation and chondrocyte‐enhanced MSC chondrogenesis (Acharya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…NP cells were harvested from the intervertebral discs (IVDs) of porcine donors ( n = 2, 3–4 months, 20–30 kg) within 3 h of sacrifice as previously described (Naqvi & Buckley, ). NP tissue was isolated and enzymatically digested in 2.5 mg mL −1 pronase solution for 1 h followed by 3 h in 0.5 mg mL −1 collagenase solution at 37 °C.…”
Section: Methodsmentioning
confidence: 99%